PENINGKATAN NILAI TAMBAH BAMBU MELALUI PENERAPAN TEKNOLOGI PENGOLAHAN BAMBU DI DESA LEGOK KECAMATAN BANTARKAWUNG KABUPATEN BREBES - Laksmi Indyastuti, Devani; lestari, Sri; Sudibyo, Gatot Heri; Fitriana, Gita Fadila (Universitas Mataram, 2024)
The problem faced in Legok Village in general is the large number of Poor Family Heads. Village monograph data in 2023 shows that out of 824 families, 54.85% of them (452 ​​families) are poor families. This village has very large bamboo plant potential, but it has not been managed properly. In this village there is a Bamboo Farmer group